Biventricular Noncompaction Cardiomyopathy in an Adult with Unique Facial Dysmorphisms: Case Report and Brief Review - Gaurav Rao; James Tauras (Case Reports in Cardiology)
Left ventricular noncompaction (LVNC) is a rare cardiomyopathy that is believed it to arise from an arrest in embryonic endomyocardial development. More recent studies suggest that it can be acquired later on in life sporadically. It may be accompanied by life-threatening complications, which are most commonly heart failure, arrhythmias, and thromboembolic events. We report a case of biventricular noncompaction cardiomyopathy in a 36-year-old man presenting for the first time with clinical heart failure as well as atrial arrhythmia. Transthoracic echocardiography (TTE) revealed LVNC with depressed ejection fraction (EF). Cardiac magnetic resonance imaging (MRI) further revealed a left atrial appendage thrombus as well as right ventricular noncompaction involvement. His physical exam was unique for a characteristic facial dysmorphisms pattern and developmental delays reminiscent of the earliest descriptions of LVNC in the pediatric population and it was rarely described in adult patients. This unique presentation underscores the importance of a better understanding of the genetics and natural course of LVNC. This will help us to elucidate the uncertainty surrounding its clinical management, discussed in a brief review of the literature following the case.